The relationship of body mass index with fasting blood glucose in type-2 diabetes mellitus - Rimadhani Ervina Tria; Mawardi Fitriana; Dewi Fitria Puspita; Purwanta Barkah Djaka; Sholikah Amanatus; Hutomo Muhammad Agita (BIO Web of Conferences)
Diabetes mellitus is a metabolic disorder caused by high blood sugar levels. Approximately 90% of diabetes cases are type 2. Indonesia ranks seventh globally with 10.7 million people affected. The increasing prevalence of diabetes mellitus is correlated with the increasing prevalence of overweight and obesity. Therefore, this research was conducted to investigate the relationship between body mass index (BMI) and fasting blood sugar (FBG) levels in type 2 diabetes patients at Umbulharjo 1 Public Health Center, Yogyakarta Province. Indonesia. Method: This research is an observational analytical study with a cross-sectional design. The sampling technique employed was purposive sampling. The total sample size for the study consisted of 325 type 2 Diabetes Mellitus patients at Umbulharjo 1 Public Health Center. Data analysis was performed using the Spearman's Rho correlation test. Result: The statistical test results indicate that the majority of type 2 diabetes mellitus patients have Obesity (55.4%) based on Body Mass Index (BMI) and diabetes (≥126) Fasting Blood Glucose (FBG) levels (99.1%). The research findings reveal no significant relationship between Body Mass Index (BMI) and Fasting Blood Glucose (FBG) levels in type 2 diabetes mellitus patients at Umbulharjo 1 Public Health Center, with a two-tailed p-value of 0.338. The strength of the relationship is very weak, with a positive correlation of 0.053. Conclusion: We highlighted that there is no significant relationship between Body Mass Index (BMI) and Fasting Blood Glucose (FBG) levels in type 2 diabetes mellitus patients at Umbulharjo 1 Public Health Center.